Three years of COVID-19 in children that attend the Mexican Social Security Institute's 1,350 child day-care centers, 2020–2023 - Martínez-Valdez, Libny; Richardson, Vesta L.; Bautista-Márquez, Aurora; Camacho Franco, Martín Alejandro; Cruz Cruz, Vicente; Hernández Ávila, Mauricio (Frontiers in Pediatrics, 2024)
Background. Studies have suggested that children are less likely than adults to develop COVID-19; however, with the emergence of SARS-CoV-2 variants, hospitalization and death due to this cause have increased among the youngest ones. Methods. Retrospective, descriptive analytical study of the COVID-19 cases, hospitalizations and deaths occurred in children under five years who attended in Child Day-Care Centers (Centros de Atención Infantil-CAIs) of the Mexican Social Security Institute (IMSS) from July 20th, 2020 to March 31st, 2023. Results were compared with Mexico's and the US's national-level data. Incidence, attack (children and workers) and mortality rates were estimated. The risks of getting sick, being hospitalized and dying due to COVID-19 were calculated by year. Results. There were 4 369 COVID-19 cases among children from IMSS CAIs; 67 (1.5%) required hospitalization and only two deaths were reported (0.04%). Both at IMSS CAIs and at a national level in Mexico and the US, the highest incidences of COVID-19 among children under five years occurred during Omicron prevalence. The attack rate among workers (32.93%) was higher than children (4.99%). Hospitalization and mortality rates in the US decreased since the anti-COVID 19 vaccine was introduced in children older than six months, unlike the rates in Mexico, where the vaccine for this age group was not available. By the year 2020, the children that attended the IMSS CAIs were 77.3% less likely to be hospitalized; 80.9% in 2021, 93.2% in 2022, and 77.7% by March 2023, compared to same age children in Mexico. In 2021, the children that attended IMSS CAIs were 90.6% less likely to die due to COVID-19, and by March 2023, this likelihood was 34.3% lower than the rest of children in this age group in Mexico. Conclusions. Children that attended IMSS CAIs had a smaller risk of hospitalization and death due to COVID-19. However, the high rates of hospitalization and death due to SARS-CoV-2 in children under five years in our country point to the need and urgency of vaccination against this virus in this age group, as well as of the adherence to strict detection and medical referral protocols.